Literature Review: Pembelajaran Berdiferensiasi Dalam Meningkatkan Hasil Belajar Matematika - Enno Triandini (PT PUSTAKA CENDEKIA GROUP, 2024)
Mathematics learning is often considered difficult by many students, especially due to its abstract nature and the need for deep conceptual understanding. One approach that can be used to address this challenge is differentiated learning. Differentiated learning aims to adjust methods, content, and learning pace according to the needs, interests, and abilities of students. This article reviews various studies that discuss the implementation of differentiated learning in the context of mathematics. The results from this literature review show that differentiated learning can improve mathematical conceptual understanding, problem-solving skills, and student motivation. However, challenges in its implementation include limitations in time, resources, and the need for specialized teacher competence. Nevertheless, differentiated learning offers great potential in improving mathematics learning outcomes when applied effectively.